The role of the pyruvate dehydrogenase complex in the regulation of human skeletal muscle fuel metabolism - Laithwaite, David (2009)
The pyruvate dehydrogenase complex (PDC) is the rate limiting step in the entry of glucose derived pyruvate into the tricarboxylic acid (TCA) cycle. As such it plays an important role in the control of the use of carbohydrate as the source of oxidative energy for skeletal muscle contraction.